Analisis Penyebab Repulping Dengan Metode Failure Mode And Effect Analysis (FMEA) Dan Fault Tree (FTA) Pada Departemen Fiberline Di PT. Toba Pulp Lestari, TBK - Zaharuddin Zaharuddin; Denny Walady Utama; Uun Novalia Harahap; Rahmat Wahyu; Alfi Dwanda Putra Mulia (Jurnal Simetri Rekayasa, 2022)
PT. Toba Pulp Lestari, Tbk is a company engaged in the pulp and kerta production business with domestic and foreign product marketing areas. PT. Toba Pulp Lestari, Tbk is one of Indonesia's largest pulp and paper producing companies. The purpose of this study is to determine the ability of the process based on existing off-grade products using the Failure Mode and Effect Analysis and Fault Tree Analysis methods to then control and analyze the causes of off-grade products and seek improvements. The results showed that there were 3 types of off-grade products: Low Brightness, Dirt Count, and Viscosity. From the calculation, the results were obtained that the largest off-grade products were X1 (viscosity) with a number of smallpox products as much as 167 tons with 26.95%, X2 (brightness) with a number of defective products with as much as 332 tons with 53.55%, and X3 (dirt count) with the number of defective products as much as 124 tons with 20%. From the FMEA results, the highest Risk Priority Number (RPN) value was obtained, namely 432 for the cause of failure due to irregular setting of the temperature and time of the digester and washing machine at Low Brightness failure. For continuous improvement, various aspects are carried out, namely human aspects, work environment, work methods, machines, and, materials.